2023
DOI: 10.1094/pdis-01-22-0243-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Fungicide Sensitivity of Colletotrichum spp. from Apple Flowers and Fruitlets in Brazil

Abstract: Glomerella leaf spot (GLS) and bitter rot (BR), caused by Colletotrichum spp., are major diseases on apple in southern Brazil. Among IPM tools for disease management in commercial orchards, fungicides remain an important component. This study aimed to identify Colletotrichum species from cultivar Eva in Paraná state orchards, evaluate their in vitro sensitivity to cyprodinil, tebuconazole, iprodione, and fluazinam, and determine the baseline in vitro sensitivity of these isolates to benzovindiflupyr and natamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Our results showed that natamycin exhibited great inhibition on the mycelia and spores of C. fructicola with a dosedependent mode, and the EC 50 and MIC values were only 1.11, 1.28, and 10 mg/L, respectively, which was even lower than that against the mycelial growth of Colletotrichum nymphaeae (5.563 mg/L) and Colletotrichum melonis (5.174 mg/L) reported previously. 17 Moreover, natamycin also displayed both protective and curative effects on apple fruit. Natamycin at 800 mg/L could entirely block the expansion of disease spots, which was nearly equal to the efficacy of flusilazole at 400 mg/L, but higher than the concentration of natamycin (200 mg/L) against Botrytis cinerea and Penicillium expansum on grape berries and jujube fruit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that natamycin exhibited great inhibition on the mycelia and spores of C. fructicola with a dosedependent mode, and the EC 50 and MIC values were only 1.11, 1.28, and 10 mg/L, respectively, which was even lower than that against the mycelial growth of Colletotrichum nymphaeae (5.563 mg/L) and Colletotrichum melonis (5.174 mg/L) reported previously. 17 Moreover, natamycin also displayed both protective and curative effects on apple fruit. Natamycin at 800 mg/L could entirely block the expansion of disease spots, which was nearly equal to the efficacy of flusilazole at 400 mg/L, but higher than the concentration of natamycin (200 mg/L) against Botrytis cinerea and Penicillium expansum on grape berries and jujube fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that natamycin exhibited great inhibition on the mycelia and spores of C. fructicola with a dose-dependent mode, and the EC 50 and MIC values were only 1.11, 1.28, and 10 mg/L, respectively, which was even lower than that against the mycelial growth of Colletotrichum nymphaeae (5.563 mg/L) and Colletotrichum melonis (5.174 mg/L) reported previously . Moreover, natamycin also displayed both protective and curative effects on apple fruit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the above techniques target one or several types of anthrax bacteria. However, the pathogenicity of different strains of pepper and their sensitivity to pesticides are different [ 25 , 26 , 27 , 28 ], which makes it difficult to prevent and control pepper anthracnose.…”
Section: Introductionmentioning
confidence: 99%
“…Good facilities provide a superior environment for flower production, and provide a good breeding and harm environment for the occurrence of diseases and pests [1] . Facilities have broken the unfavorable conditions of pests and diseases over winter and summer, so that pests and diseases have achieved annual reproduction and infestation, which has caused a greater threat to the plant flower production, not only destroying the ornamental value of flowers, but also causing greater economic losses to the producers, which is not conducive to the intensive and large-scale production of flowers [2] . This study analyzed the occurrence characteristics of plant pests and diseases, explored the dominant diseases and pests and their occurrence conditions, and formulated comprehensive prevention and control countermeasures of facility dominant diseases and pests, aiming at providing strong technical support for the healthy development of facility flowers in Hubei Province.…”
Section: Introductionmentioning
confidence: 99%